Analisis Klaim Reasuransi Jiwa pada Laporan Laba Rugi Pasca Pandemi Covid-19 tahun 2020: (Studi Kasus PT. Reasuransi Indonesia utama (persero)) - Apry Linda Diana; Desi Rezky Amalia; Mochamad Yusuf (JASS (Journal of Accounting for Sustainable Society), 2023)
This study aims to determine the effect of Life Reinsurance claims on the company's profit and loss statements after the Covid-19 pandemic in 2020 and to find out the company's strategy in dealing with problems that occur in the income statement of PT. Reinsurance Indonesia Utama (Persero) during the 2020 Covid-19 pandemic. This study uses a quantitative descriptive approach, namely collecting the necessary data from the company PT. Reinsurance Indonesia Utama (Persero) in the accounting division area related to the company's 2020 profit (loss) report in the Covid-19 pandemic conditions. The results of this study prove that there is an increase in the claim expense to the company, the increase in claims is a result of the poor performance of several products, the majority of which are contributed by the Credit Life Insurance (AJK) business in 2020 due to the impact of the pandemic and there are Covid-19 claims such as cover vaccines, self-isolation, and Covid-19 treatment. As a result of the increase in claims expense, it will directly affect the value of the company's Underwriting - Net (HUB) results, high claims payments will affect the company's solvency level as a result of which the company's profit achievement in 2020 has decreased when compared to the company's profit income in 2019.